1999
DOI: 10.1029/1999ja900106
|View full text |Cite
|
Sign up to set email alerts
|

A search for small comets with the Naval Space Command radar

Abstract: Abstract. We have searched for the hypothetical small comets proposed by Frank et al. [1986a, b] and Frank and Sigwarth [1993] using the world's most powerful radar in terms of gain-aperture product. The Naval Space Surveillance System can detect most space objects in low Earth orbit with radar cross sections (RCSs) of 0.1 m 2 or larger; at higher altitudes of the order of 10,000-20,000 km the radar can detect objects with RCSs of 1 m 2. We carried out detailed first-principle calculations of the RCS of sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…In a previous paper [Knowles et al, 1999; hereinafter referred to as KMGG], we showed that during a 6-week observing period, the Naval Space Command Radar "Fence" should have detected thousands of small comets with the properties proposed by Frank et al [1986a, b] and Frank and Sigwarth [1993]. Frank and Sigwarth [this issue] dispute our conclusions because they believe that our estimates of the expected radar cross section were based on a misrepresentation of their model of the properties of small comets.…”
Section: Introductionmentioning
confidence: 75%
“…In a previous paper [Knowles et al, 1999; hereinafter referred to as KMGG], we showed that during a 6-week observing period, the Naval Space Command Radar "Fence" should have detected thousands of small comets with the properties proposed by Frank et al [1986a, b] and Frank and Sigwarth [1993]. Frank and Sigwarth [this issue] dispute our conclusions because they believe that our estimates of the expected radar cross section were based on a misrepresentation of their model of the properties of small comets.…”
Section: Introductionmentioning
confidence: 75%
“…We have used values for the physical parameters for small comets in the published literature and the corresponding radar cross sections as given by Knowles et al [1999] and conclude that detection of the small comets with the Naval radar is very unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…In order to increase the radar cross section to values above those at and below the thresholds shown in our Figures I and 2, Knowles et al [1999] claim that there is no published information concerning the size distributions of small comets and assume large cometary diameters of tens of meters. This claim is incorrect because information in refereed papers concerning the size distributions of the small comets was obtained by the direct optical detections with the ground-based Spacewatch Telescope [Yeates, 1989;Frank et al, 1990;Frank and Sigwarth, 1993].…”
Section: Size Distributions Of Small Cometsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure 1 shows a snapshot of the detections by the Naval Space Surveillance (NAVSPASUR) radar fence, showing the dense LEO region, along with the Global Positioning Satellites (GPS) for perspective [Knowles et al, 1999a[Knowles et al, , 1999b. The U.S. Space Command continues to produce TLEs for most known LEO objects by fitting a time series of observations like those in Figure 1 with a ''Simplified General Perturbations'' orbit propagator, now known as SGP4.…”
Section: Introductionmentioning
confidence: 99%